Angiotensin-(1-7) protective effects in neurocognitive disorders: molecular mechanisms to therapeutic implications - Lucas, Lillia C.; Kimbark, Katherine D.; Vernail, Victoria L.; Silberman, Yuval; Arnold, Amy C. (Frontiers in Physiology, 2025)
Cognition broadly refers to the ability to perform mental processes such as learning and memory, attention, emotional awareness, and higher-order thinking. Cognitive deficits can result from the normal aging process or other factors such as disease progression or injury. While the exact etiology is not fully understood, emerging evidence suggests that enhanced inflammatory and oxidative stress processes during aging can dramatically decrease cognitive function in older adults, as well as contribute to the onset and progression of neurocognitive disorders. Current treatments for neurocognitive disorders have limited efficacy and typically focus on symptom attenuation rather than targeting intrinsic pathophysiology. With the rising aging population, there is a critical need to identify novel treatment approaches that target the underlying inflammatory and oxidative mechanisms contributing to neurocognitive disorders. In this regard, the renin-angiotensin system (RAS) may provide an ideal target, as this hormonal system has been implicated in the regulation of inflammatory and oxidative responses to impact cognitive functions. While most research to date has focused on the deleterious role of angiotensin (Ang) II pathways in age-related cognitive decline and neurocognitive disorders, more recent evidence has examined the potential for targeting Ang-(1-7), a protective hormone of the RAS, to counteract these effects. This review highlights emerging evidence showing that activation of Ang-(1-7) pathways reduces inflammation and oxidative stress and may provide a novel target to improve cognitive function and elicit neuroprotection, in the context of both aging and neurocognitive disorders.